Spitzer observations of SN 2014J and properties of mid-IR emission in Type Ia supernovae. Issue 3 (7th January 2017) - Johansson, J.; Goobar, A.; Kasliwal, M. M.; Helou, G.; Masci, F.; Tinyanont, S.; Jencson, J.; Cao, Y.; Fox, O. D.; Kromer, M.; Amanullah, R.; Banerjee, D. P. K.; et al.
Abstract: SN 2014J in M 82 is the closest Type Ia supernova (SN Ia) in decades. The proximity allows for detailed studies of supernova physics and provides insights into the circumstellar and interstellar environment. In this work, we analyse Spitzer mid-infrared (mid-IR) data of SN 2014J in the 3.6 and 4.5 μm wavelength range, together with several other nearby and well-studied SNe Ia. We compile the first composite mid-IR light-curve templates from our sample of SNe Ia, spanning the range from before peak brightness well into the nebular phase. Our observations indicate that SNe Ia form a very homogeneous class of objects at these wavelengths. Using the low-reddening supernovae for comparison, we constrain possible thermal emission from circumstellar dust around the highly reddened SN 2014J. We also study SNe 2006X and 2007le, where the presence of matter in the circumstellar environment has been suggested. No significant mid-IR excess is detected, allowing us to place upper limits on the amount of pre-existing dust in the circumstellar environment. For SN 2014J, M dust ≲ 10 − 5 M⊙ within r dust ∼ 10 17 cm, which is insufficient to account for the observed extinction. Similar limits are obtained for SNe 2006X and 2007le.